A multicenter single‐arm objective performance criteria trial evaluating the efficacy and safety of a dedicated venous sinus thrombectomy device for severe cerebral venous sinus thrombosis - Shadamu Yusuying; Yan Wu; Ming Li; Jiangang Duan; Jian Chen; Yujiao Chen; Chen Zhou; Hetao Bian; Chuanhui Li; Chuanjie Wu; Ran Meng; Xunming Ji (Neuroprotection)
Abstract Aim Approximately 21% of patients with cerebral venous sinus thrombosis (CVST) are refractory to anticoagulation treatment and face poor prognosis. These patients may benefit from endovascular therapy. Although numerous studies have reported promising results with endovascular therapy, it remains challenging to obtain convincing evidence of its efficacy and safety due to the unique challenges posed by CVST, such as larger vessel diameters, distinct pathophysiology, and substantial clot burden. Therefore, dedicated endovascular therapy tools should be developed specifically for CVST. This study aimed to evaluate the efficacy and safety of a dedicated venous sinus thrombectomy device in patients with acute or subacute CVST. Methods This prospective, multicenter, single‐arm trial utilized an objective performance criterion design. Enrolled patients received treatment with a dedicated venous sinus thrombectomy device to recanalize occluded sinuses or veins. The primary objective was to compare the immediate postoperative recanalization rate with a preset target value to determine whether the device met the clinical application needs. The trial plans to enroll 146 patients from 11 tertiary medical centers in China. Discussion This trial is expected to fill a critical gap in endovascular treatments for CVST and support the development of reliable, dedicated thrombectomy devices for future studies.